PERAN LITERASI KEUANGAN DAN INKLUSI PERBANKAN DALAM MENDORONG AKSES PEMBIAYAAN UMKM - Pratiwi, I Gusti Ayu Made Agung Mas Andriani; Kusmawan, I Made Hary; Suarbawa, I Wayan; Utomo, Rochmad Bayu Utomo (Universitas Tabanan, 2025)
Access to financing remains a significant barrier for Micro, Small, and Medium Enterprises (MSMEs) in developing their businesses in Indonesia. Two crucial factors in overcoming this barrier are financial literacy and banking inclusion. This study examines the relationship between bank financing, financial literacy, and banking inclusion through a literature review approach. The findings indicate that high financial literacy enables MSME actors to understand and manage financial information more effectively, thereby increasing their confidence in applying for loans. Banking inclusion, on the other hand, provides broader access for MSME actors to utilize various formal financial services, supporting the growth and sustainability of their businesses. The synergy between financial literacy and banking inclusion creates a more inclusive ecosystem, although challenges such as stringent collateral requirements and complex loan application processes still need to be addressed. Effective collaboration among financial institutions, government, and community organizations is essential to strengthen financial literacy and banking inclusion. Financial education programs tailored to the needs of MSMEs are expected to enhance their financial knowledge and skills, making them better prepared to seize financing opportunities. Sustainable collaborative efforts among various stakeholders are key to improving access to financing for MSMEs, thereby supporting inclusive and sustainable national economic growth.